Characterization of Nivalenol-Producing Fusarium asiaticum That Causes Cereal Head Blight in Korea - Jang, Ja Yeong (Plant Pathol J, 2019)
Fusarium asiaticum of the F. graminearum species complex causes head blight in small-grain cereals. The nivalenol (NIV) chemotypes of F. asiaticum is more common than the deoxynivalenol (DON) chemotypes of F. asiaticum or F. graminearum in Korea. To understand the prevalence of F. asiaticum–NIV in Korean cereals, we characterized the biological traits of 80 cereal isolates of F. asiaticum producing NIV or 3-acetyl-deoxynivalenol (3-ADON), and 54 F. graminearum with 3-ADON or 15-acetyl-deoxynivalenol (15-ADON). There was no significant difference in mycelial growth between the chemotypes, but F. asiaticum isolates grew approximately 30% faster than F. graminearum isolates on potato dextrose agar. Sexual and asexual reproduction capacities differed markedly between the two species. Both chemotypes of F. graminearum (3-ADON and 15-ADON) produced significantly higher numbers of perithecia and conidia than F. asiaticum–NIV. The highest level of mycotoxins (sum of trichothecenes and zearalenone) was produced by F. graminearum–3-ADON on rice medium, followed by F. graminearum–15-ADON, F. asiaticum–3-ADON, and F. asiaticum–NIV. Zearalenone levels were correlated with DON levels in some chemotypes, but not with NIV levels. Disease assessment on barley, maize, rice, and wheat revealed that both F. asiaticum and F. graminearum isolates were virulent toward all crops tested. However, there is a tendency that virulence levels of F. asiaticum–NIV isolates on rice were higher than those of F. graminearum isolates. Taken together, the phenotypic traits found among the Korean F. asiaticum–NIV isolates suggest an association with their host adaptation to certain environments in Korea.